2011
DOI: 10.1186/1476-4598-10-64
|View full text |Cite
|
Sign up to set email alerts
|

New Topoisomerase I mutations are associated with resistance to camptothecin

Abstract: BackgroundTopoisomerase I (TOP1) is a nuclear enzyme that catalyzes the relaxation of supercoiled DNA during DNA replication and transcription. TOP1 is the molecular target of camptothecin and related drugs such as irinotecan and SN38 (irinotecan's active metabolite). Irinotecan is widely used as an anti-cancer agent in the treatment of metastatic colon cancer. However, its efficacy is often limited by the development of resistance.MethodsWe previously established several SN38 resistant HCT116-derived clones t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 29 publications
0
60
0
1
Order By: Relevance
“…The correlation between TOP1cc formation and DNA damage response has been reported in a wide variety of cancer cells when exposed to topoisomerase I inhibitors [27,28]. Moreover, it has been reported that in SN38 (an active metabolite of irinotecan) resistant cancer cell clones, the presence of topoisomerase I mutations did not change the expression level and activity of topoisomerase I, but decrease the TOP1cc associated with a reduction in DSBs when challenged with SN38 [29]. These studies suggest that the formation of TOP1cc is critical to DNA damage and apoptosis caused by topoisomerase I inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between TOP1cc formation and DNA damage response has been reported in a wide variety of cancer cells when exposed to topoisomerase I inhibitors [27,28]. Moreover, it has been reported that in SN38 (an active metabolite of irinotecan) resistant cancer cell clones, the presence of topoisomerase I mutations did not change the expression level and activity of topoisomerase I, but decrease the TOP1cc associated with a reduction in DSBs when challenged with SN38 [29]. These studies suggest that the formation of TOP1cc is critical to DNA damage and apoptosis caused by topoisomerase I inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Levels of SN-38 were found in the tumor of animals given IMMU-132, and as the topoisomerase I activity of SN-38 is enhanced in Sphase cells, maintaining an SN-38 presence for 3 days compared with 8 hours would be another advantage. Because resistance to irinotecan therapy can occur for a variety of reasons (24)(25)(26)(27), it is uncertain whether the ability to enhance SN-38 delivery with this ADC will affect resistance in a clinically meaningful manner. We Figure 3.…”
Section: Discussionmentioning
confidence: 99%
“…These cell lines have been obtained in 2000, were amplified and frozen, and one aliquot of each was thawed for this project, although no authentication was done by the authors. The SN-38-resistant HCT116 and SW48 cell clones were obtained as previously described (7,9,12). Briefly, the reference SN-38-sensitive HCT116 cell clone (HCT116-s) was exposed to 10 nmol/L SN-38 and cloned to obtain the HCT116-SN6 and HCT116-A2 clones.…”
Section: Cell Linesmentioning
confidence: 99%
“…Like other camptothecin derivatives, SN-38 is an inhibitor of topoisomerase I, a nuclear enzyme needed for replication and transcription through relaxation of supercoiled DNA (4,5). Cellular mechanisms causing irinotecan/SN-38 resistance have been reported for each step of the CPT-11 pathway (6)(7)(8)(9). Among them, it has been shown that cultured cells that are resistant to camptothecin derivatives have reduced intracellular drug accumulation, mediated by the ATPbinding cassette (ABC) transporter ABCG2 (10), especially in colon cancer cells (11,12).…”
Section: Introductionmentioning
confidence: 99%